St. George and St. Michael - MacDonald, George, 1824-1905 (Salt Lake City, UT : Project Gutenberg, 2004)
"St. George and St. Michael" by George MacDonald is a historical novel written during the late 19th century. The story unfolds against a backdrop of societal upheaval and political strife, focusing on the lives of its central characters, particularly Dorothy Vaughan and Richard Heywood, as they navigate the complex moral and ideological landscapes of their time. The beginning of the novel introduces a somber autumn afternoon where Dorothy and her mother converse with Mr. Herbert, a clergyman, about the troubling state of the world, reflecting on themes of morality and the moral challenges posed by authority. As the rain falls outside, an atmosphere of gloom is punctuated by the rays of the setting sun, mirroring the tension in the interpersonal dynamics that emerges when Richard attempts to express his feelings for Dorothy. Their conversation reveals their differing perspectives on loyalty to the Church versus emerging political beliefs, setting the stage for deeper ideological conflicts that may challenge both their friendship and their futures amidst the looming trials of their era. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Charles Aldarondo, Charles Franks and the Distributed Proofreading Team
Keywords: Great Britain -- History -- Civil War, 1642-1649 -- Fiction